Clarification of the correct authorship of Cremanthodium prattii, with lectotypification of Senecio prattii - Chi, Xiao-Rui; Wang, Long (Phytotaxa, 2024)
Senecio prattii Hemsley (1896: pl. 2491) was described based on three collections, i.e. A. E. Pratt 492, A. E. Pratt 548 and A. E. Pratt 593, all from Kangding, western Sichuan, China. After its publication, it was considered as a distinct member of Cremanthodium Bentham (1873: 37) and its independent specific status has been widely recognized by all the subsequent authors, including Dunn (1911), Good (1929), Handel-Mazzetti (1938), Hu (1966), Koyama (1968), Liu (1989), Chen & Li (1994), Liu & Illarionova (2011), and Chen (2019).